Development of Agrobacterium-Mediated for Chi2;1 Promoter Analysis of llycopersicon Esculentum on Mt11 - A. Rahman, Siti Suhailah (2005)
Improvement of Agrobacterium-mediated transformation system (AMT) in MTll cultivar is required to achieve higher efficiency of gene transfer to produce transgenic plants of MT11. Various concentrations of kinetin and zeatin were tested for cultivar MTll and VF36 explants, up to 100% of the explants are capable of producing calli from cotyledon and hypocotyls. Kinetin at 5 mg/L was highly significant (p0.01) in terms of the largest number of shoot regeneration from cotyledons explants of MTll cultivar. The use of 2 mg/L zeatin was highly significant (p0.01) for shoot elongation of American variety, VF36. The addition of ascorbic acid @re- and post- inoculation with Agrobacterium) and acetosyringone were significant (p0.01) for cell recovery and in enhancing the development of putatively transformed plantlets of MTll and VF36 tomato cultivar. The combined interactions between pBY4.1 and acetosyringone was found to be highly significant (pc0.01) in terms of number of putatively transformed plants obtained. Kanamycin at 100 mg/L is the most suitable minimal inhibition concentration to be use in the transformation. Agrobacterium tumefaciens strain LBA4404 is more suitable to be use in the transformation system compared to GV2260 strain for MTl 1 cultivar. The PCR amplification technique determined that the full length of Chi2;l promoter (1336 bp) and the deletions: pBY2.3 (226 bp), pBY4.1 (435 bp), pBY6.1 (616 bp) and pBY8.1 (865 bp) showed the 1.8 kb GUS genes after gel electrophoresis. The pistils from the transgenic plants showed the expression of GUS genes blue stained in the transmitting tract, except for pBYO.5 construct (58 bp) and the control. Southern blots analysis showed pBY4.1 deletion had the strongest signal. Seedlings from pBY4.1 flower were tested and confirmed that the foreign integrated genes is inherited